Skin malignancies in ibadan: a comparative study (2008)
Background: The incidence of skin cancers is on the rise in Caucasians. There is also an observed increase in the diagnosis of basal cell carcinoma in blacks. This study evaluated the pattern of skin cancers in Southwestern Nigeria and compared the trends with what obtained three decades earlier. Patients and Methods: A retrospective study of skin malignancies in Ibadan, Nigeria, based on Cancer Registry data was performed. Between January 1981 and December 2000, four hundred and ninety four (494) histologically confirmed cases of skin malignancies were recorded in the Ibadan Cancer Registry. Result: The commonest lesion recorded was squamous cell carcinoma accounting for 40.5% (200) of the cases. This was followed by malignant melanoma (25.1%), dermatofibrosarcoma protuberance (9.5%), Kaposi's sarcoma 8.3% and basal cell carcinoma (6.7%). Less common histological types included adenocarcinoma, undifferentiated carcinoma, mucoepidermoid carcinoma, adenoid cystic carcinoma, fibrosarcoma and mycosis fungoides. Conclusion: Though squamous cell carcinoma is still the leading cause of skin malignancy in Ibadan. There is a statistically significant decline in its proportion and a statistically significant increase in the proportion of basal cell carcinoma, compared to proportions documented three decades earlier. This change is due to subtle differences in aetiology. The proportion of Kaposi's sarcoma has also increased probably due to increasing HIV infection rate. Hospital prevalence for basal cell carcinoma and malignant melanoma did not show the progressive increase in incidence noted among Caucasians.